Parenting Patterns in Nurturing Children's Character in the Era of Covid-19 - Adam Mudinillah; Lusiana Rahmadani Putri (State Institute of Islamic Studies Batusangkar, 2023)
As a nation that upholds traditional values and is internationally recognized for its etiquette and politeness, Indonesia stands out in the context of the Covid-19 pandemic, which has significantly impacted the character of students across much of the world. The aim of this research is to understand the motivations underlying individuals' actions in shaping a child's character during the Covid-19 era through Islamic education. The current study employs a quantitative methodology utilizing a survey model and written questionnaires. The survey used for this research was conducted online. The results of this study indicate that students' self-confidence increases when teachers use dolls to engage children during the Covid-19 era in the learning process. The findings of this research clearly demonstrate that the support provided by parental parenting styles to teachers in the process of Islamic education in the classroom greatly enhances students' achievements. Therefore, the conclusion of this research is limited to examining the role of youth in the Covid-19 era within Islamic education. Thus, the researcher hopes that future researchers can investigate the role of youth in the Covid-19 era, incorporating the findings of this research into other fields of study.